Preparation method and application of ultrahigh-tensile conductive hydrogel material
The ultra-high stretchable conductive hydrogel addresses mechanical and freezing issues by integrating MXene nanosheets into a polymer network, enhancing mechanical properties and antifreeze capabilities, enabling effective human motion detection.
Patent Information
- Application Number
- CN202411297594.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conductive hydrogels suffer from poor mechanical properties due to carbon material stacking, leading to brittle fracture during stretching, and freeze at sub-zero temperatures, limiting their application in large-scale motion monitoring.
A method involving the preparation of an ultra-high stretchable conductive hydrogel using CMC-Na/PAM/MXene, where MXene nanosheets are interspersed in a polymer network through hydrogen bonding, enhanced by solvent replacement with ethylene glycol to improve mechanical properties and antifreeze capabilities.
The hydrogel achieves a tensile strain of up to 5928% at room temperature and 3328% at -20°C, maintaining mechanical integrity and sensing performance, with excellent sensitivity and stability for detecting human movements.
Smart Images

Figure CN119119368A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials and sensors, and specifically relates to a preparation method of an ultra-high tensile conductive hydrogel material and application thereof. Background Art
[0002] Conductive hydrogel is a viscoelastic material composed of hydrophilic polymers. It has good conductivity, adjustable mechanical properties and good biocompatibility, and can well simulate the various functions of human skin. When conductive hydrogel is used as a flexible sensor, it can be deformed freely according to different movement forms, and has excellent mechanical durability, and can maintain stable performance after repeated use. With its unique flexibility and efficient and low-cost manufacturing process, hydrogel has broad application prospects in the fields of electronic skin, wearable sensors, soft robots and human-computer interaction.
[0003] However, the poor mechanical properties of carbon-based conductive hydrogels severely limit their application in large-scale motion monitoring. This is because the stacking of carbon materials will destroy the gel network of the hydrogel, which is prone to brittle fracture during stretching. A feasible method is to improve the dispersibility of carbon materials in the gel network so that they will not stack on each other during stretching. At the same time, the antifreeze properties of conductive hydrogels are also extremely important in their applications. At sub-zero temperatures, the water in the hydrogel will freeze, severely limiting the mechanical properties and sensing performance.
[0004] Therefore, how to develop conductive hydrogels with ultra-high mechanical properties and antifreeze properties is an important issue. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing an ultra-high stretchable conductive hydrogel material and its application, which is used to solve the problems in the prior art that the stacking of carbon materials will destroy the gel network of the hydrogel and the water in the hydrogel will freeze at sub-zero temperatures, which seriously limits the mechanical properties and sensing performance.
[0006] In order to achieve the above objectives, the present invention adopts the following technical solutions: The present invention provides a method for preparing an ultra-high stretchable conductive hydrogel material, which specifically comprises the following steps: (1) Preparation of CMC-Na / PAM / MXene conductive hydrogel: At room temperature, acrylamide (AM), N,N'-methylenebisacrylamide (MBA), ammonium persulfate (APS) and MXene organic dispersion were added to sodium carboxymethyl cellulose (CMC-Na) solution and stirred evenly to prepare a pre-liquid.
[0007] (2) The prefabricated liquid prepared in step 1 is transferred into a mold and polymerized in an oven for 2 to 6 hours to obtain an interpenetrating network CMC-Na / PAM / MXene conductive hydrogel.
[0008] (3) The prepared interpenetrating network CMC-Na / PAM / MXene conductive hydrogel was immersed in ethylene glycol aqueous solutions of different concentrations. After solvent replacement, an ultra-high stretchable conductive hydrogel was obtained.
[0009] Furthermore, in step (1), the MXene organic dispersion includes MXene and N,N-dimethylformamide, wherein the ratio of MXene to N,N-dimethylformamide is 20-100 mg:2.5 mL.
[0010] Furthermore, in step (1), the acrylamide solution is prepared by adding acrylamide to distilled water and stirring at 25° C. until the acrylamide is completely dissolved; the concentration of the acrylamide solution is 23 wt %.
[0011] Preferably, in step (1), the dosage ratio of sodium carboxymethyl cellulose (CMC-Na) solution, acrylamide (AM), N,N-methylenebisacrylamide (MBA), ammonium persulfate (APS), MXene organic dispersion and distilled water is 0.25-1.25 g: 3 g: 0.02 g: 2 g: 2.5 mL: 7.5 mL.
[0012] Furthermore, in step (2), the oven condition is vacuum and the temperature is controlled at 40-60°C.
[0013] Furthermore, in step (3), the concentration of the ethylene glycol aqueous solution is 20-60 wt%.
[0014] Furthermore, in step (3), the solvent replacement is performed by completely immersing the hydrogel in an ethylene glycol aqueous solution for 2 to 4 hours, thereby partially replacing the water molecules in the hydrogel with the ethylene glycol solution.
[0015] The present invention also provides the use of the ultra-high stretchable conductive hydrogel in the preparation of strain-type flexible sensors.
[0016] During the application process, the ultra-high stretchable conductive hydrogel is acrylamide monomer that first undergoes in-situ free radical polymerization to form an interpenetrating network with CMC-Na, and then the MXene nanosheets are interspersed in the polymer network. The polymer chains fix the MXene nanosheets in the gel matrix. The polymer network of PAM in the ultra-high stretchable conductive hydrogel interacts with the functional groups containing oxygen and fluorine atoms in the MXene nanosheets through hydrogen bonds, further forming a dynamic cross-linked network.
[0017] In summary, due to the adoption of the above technical solution, the beneficial technical effects of the invention are: During the preparation process, the present invention utilizes a PAM chemically cross-linked network to form an interpenetrating network with CMC-Na, interpenetrating MXene nanosheets into the polymer network, and the polymer chains fix the MXene nanosheets in the gel matrix. The polymer network of PAM in the hydrogel interacts with the functional groups containing oxygen and fluorine atoms in the MXene nanosheets through hydrogen bonds, further forming a dynamic cross-linked network.
[0018] During the preparation process, the present invention utilizes the synergistic effect of two organic solvents to enhance the interfacial effect between MXene nanosheets and the gel network, further improving the mechanical properties of the hydrogel, with a tensile strain of up to 5928% and a maximum tensile stress of 40 kPa. At the same time, it also has good anti-drying and anti-freezing capabilities. After being stored at room temperature for 100 days, the tensile strain can reach 2082%, and even at -20°C, the tensile strain can reach 3328%.
[0019] The MPAE conductive composite hydrogel prepared in the present invention can accurately monitor tiny movement information of the human body, such as finger bending, wrist and elbow movement, muscle vibration and eyelid twitching, and has good sensing performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The preparation process of ultrahigh stretchable conductive hydrogel.
[0021] Figure 2 Tensile stress-strain curves of ultra-high stretchable conductive hydrogel at 25℃ and -20℃.
[0022] Figure 3 Resistance change of ultrahigh stretchable conductive hydrogel after 150 cycles of cyclic stretching at 50% strain.
[0023] Figure 4 The resistance signal change obtained by attaching the ultra-high stretchable conductive hydrogel to the human wrist for sensing testing.
[0024] Figure 5 The resistance signal change obtained by attaching the ultra-high stretchable conductive hydrogel to the human cheek for sensing testing. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the invention more clear, the invention is further described in detail below in combination with the embodiments. It should be understood that the specific embodiments described here are only used to explain the invention and are not used to limit the invention. Example 1
[0026] At room temperature, 0.25g CMC-Na solution and 3g acrylamide (AM) were mixed together. Subsequently, MBA solution (0.02g) and APS solution (2g) were added to the above solution and mixed evenly to obtain a pre-gel solution. Then, 2.5mL MXene organic dispersion and 7.5mL distilled water were added to the above solution to make it dispersed evenly. Finally, the pre-gel solution was transferred to a rectangular mold and reacted in a vacuum oven at 60°C for 4h to obtain an interpenetrating network CMC-Na / PAM / MXene conductive hydrogel. It was soaked in ethylene glycol aqueous solutions of different concentrations, and after 4h of solvent replacement, an ultra-high stretchable conductive hydrogel was obtained.
[0027] Figure 1 This is the preparation process of CMC-Na / PAM / MXene conductive hydrogel. As can be seen from the figure, in the aqueous solution doped with sodium carboxymethyl cellulose, the acrylamide monomer first undergoes in situ free radical polymerization to form an interpenetrating network with CMC-Na, and then the MXene nanosheets are interspersed in the polymer network. The polymer chains fix the MXene nanosheets in the gel matrix. The polymer network of PAM in the ultra-high stretchable conductive hydrogel interacts with the functional groups containing oxygen and fluorine atoms in the MXene nanosheets through hydrogen bonds, further forming a dynamic cross-linked network. Example 2
[0028] At room temperature, 0.65g CMC-Na solution and 3g acrylamide (AM) were mixed together. Subsequently, MBA solution (0.02g) and APS solution (2g) were added to the above solution and mixed evenly to obtain a pre-gel solution. Then, 2.5mL MXene organic dispersion and 7.5mL distilled water were added to the above solution to make it dispersed evenly. Finally, the pre-gel solution was transferred to a rectangular mold and reacted in a vacuum oven at 60°C for 5h to obtain an interpenetrating network CMC-Na / PAM / MXene conductive hydrogel. It was soaked in ethylene glycol aqueous solutions of different concentrations, and after 4h of solvent replacement, an ultra-high stretchable conductive hydrogel was obtained.
[0029] Figure 2 The tensile stress-strain curve of ultra-high stretchable conductive hydrogel at 25°C and -20°C. Since the hydrogel contains a large amount of water, it is easy to freeze at low temperatures, resulting in reduced mechanical properties and easy brittle fracture when stretched by external force. After being stored at -20°C for 24 hours, the ultra-high stretchable conductive hydrogel still maintains good mechanical properties, and the stretching length can reach more than 33 times the initial length. The results show that the ultra-high stretchable conductive hydrogel can maintain good mechanical properties at lower temperatures. Example 3
[0030] At room temperature, 1.0g CMC-Na solution and 3g acrylamide (AM) were mixed together. Subsequently, MBA solution (0.02g) and APS solution (2g) were added to the above solution and mixed evenly to obtain a pre-gel solution. Then, 2.5mL MXene organic dispersion and 7.5mL distilled water were added to the above solution to make it dispersed evenly. Finally, the pre-gel solution was transferred to a rectangular mold and reacted in a vacuum oven at 60°C for 6h to obtain an interpenetrating network CMC-Na / PAM / MXene conductive hydrogel. It was soaked in ethylene glycol aqueous solutions of different concentrations, and after 4h of solvent replacement, an ultra-high stretchable conductive hydrogel was obtained.
[0031] The hydrogel prepared above was cut into 3*1*1cm cuboids to form flexible sensors. Figure 3 This is the resistance change rate of the ultra-high stretchable conductive hydrogel after 150 cycles of stretching at 50% strain. It can be seen that the ultra-high stretchable conductive hydrogel shows high sensitivity and good repeatability in the 50% stretching cycle test. Example 4
[0032] At room temperature, 1.25g CMC-Na solution and 3g acrylamide (AM) were mixed together. Subsequently, MBA solution (0.02g) and APS solution (2g) were added to the above solution and mixed evenly to obtain a pre-gel solution. Then, 2.5mL MXene organic dispersion and 7.5mL distilled water were added to the above solution to make it dispersed evenly. Finally, the pre-gel solution was transferred to a rectangular mold and reacted in a vacuum oven at 60°C for 6h to obtain an interpenetrating network CMC-Na / PAM / MXene conductive hydrogel. It was soaked in ethylene glycol aqueous solutions of different concentrations, and after 4h of solvent replacement, an ultra-high stretchable conductive hydrogel was obtained.
[0033] The ultra-high stretchable conductive hydrogel hydrogel exhibits excellent sensing sensitivity and signal stability, and is resistant to low temperatures and has the characteristics of moisture retention. Given these excellent properties, it can be placed on human skin and accurately detect human motion. A digital multimeter is connected to the conductive hydrogel to make a flexible sensing device for human motion detection. The ultra-high stretchable conductive hydrogel hydrogel is initially applied to detect the bending of the human wrist. Figure 4 The resistance signal test of the wrist shows regular changes with the regular movement of the wrist. It is worth noting that when the bending angle returns to the initial state, the resistance of the ultra-high stretchable conductive hydrogel also returns to the initial value, and its relative resistance change rate is stable, which shows that the hydrogel has good stability and can detect human movement throughout the day. Example 5
[0034] At room temperature, 1.25g CMC-Na solution and 3g acrylamide (AM) were mixed together. Subsequently, MBA solution (0.02g) and APS solution (2g) were added to the above solution and mixed evenly to obtain a pre-gel solution. Then, 2.5mL MXene organic dispersion and 7.5mL distilled water were added to the above solution to make it evenly dispersed. Finally, the pre-gel solution was transferred to a rectangular mold and reacted in a vacuum oven at 60°C for 6h to obtain an interpenetrating network CMC-Na / PAM / MXene conductive hydrogel. It was soaked in ethylene glycol aqueous solutions of different concentrations, and after 4h of solvent replacement, an ultra-high stretchable conductive hydrogel was obtained.
[0035] In order to further study the ability of ultra-high stretchable conductive hydrogel to detect human skin, the ultra-high stretchable conductive hydrogel was attached to the cheek, and the movement of the cheek skin was driven by chewing gum to detect its movement. When chewing gum, it will drive the skin on both sides of the cheek to vibrate. When the skin stretches outward, it will apply pressure to the ultra-high stretchable conductive hydrogel, compressing the gel network and reducing the resistance. When the skin stretches inward, the gel network returns to its initial position and the resistance increases. Figure 5 The ultra-high stretchable conductive hydrogel was attached to the human cheek for sensing testing. The test results showed that the ultra-high stretchable conductive hydrogel can accurately detect tiny movement information of the human body and can be used as a strain sensor to provide real-time feedback of human movement information.
[0036] The above description is a preferred embodiment of the invention and is not intended to limit the invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the invention should be included in the protection scope of the invention.
Claims
1. A method for preparing an ultra-high tensile conductive hydrogel material, characterized in that: The specific steps include: Step (1) Preparation of CMC-Na / PAM / MXene conductive hydrogel: At room temperature, a 23 wt% acrylamide (AM) solution, N,N'-methylenebisacrylamide (MBA), ammonium persulfate (APS) and MXene organic dispersion were added to a sodium carboxymethyl cellulose solution (CMC-Na) and stirred to prepare a preformed solution. Step (2) transferring the prefabricated liquid prepared in step 1 into a mold, and polymerizing the prefabricated liquid in an oven for 2 to 6 hours to obtain an interpenetrating network CMC-Na / PAM / MXene conductive hydrogel; Step (3) The interpenetrating network CMC-Na / PAM / MXene conductive hydrogel prepared in step 2 is immersed in ethylene glycol aqueous solutions of different concentrations, and after solvent replacement, an ultrahigh stretchable conductive hydrogel is obtained.
2. The method for preparing an ultra-high tensile conductive hydrogel material according to claim 1, wherein: In step (1), the MXene organic dispersion includes MXene and N,N-dimethylformamide, wherein the ratio of MXene to N,N-dimethylformamide is 20-100 mg:2.5 mL.
3. The method for preparing an ultra-high stretchable conductive hydrogel material according to claim 1, wherein: In step (1), the method for preparing the acrylamide solution with a concentration of 23 wt% is: adding acrylamide to distilled water and stirring at 25°C until the acrylamide is completely dissolved to obtain an acrylamide solution with a concentration of 23 wt%.
4. The method for preparing an ultra-high stretchable conductive hydrogel material according to claim 1, wherein: In step (1), the dosage ratio of sodium carboxymethyl cellulose (CMC-Na) solution, acrylamide (AM), N,N-methylenebisacrylamide (MBA), ammonium persulfate (APS), MXene organic dispersion and distilled water is 0.25-1.25 g:3 g:0.02 g:2 g:2.5 mL:7.5 mL.
5. The method for preparing an ultra-high stretchable conductive hydrogel material according to claim 1, wherein: In the step (2), the oven condition is vacuum and the temperature is controlled at 40-60°C.
6. The method for preparing an ultra-high stretchable conductive hydrogel material according to claim 1, wherein: In step (2), the concentration of the ethylene glycol aqueous solution is 20-60 wt%.
7. The method for preparing an ultra-high stretchable conductive hydrogel material according to claim 1, wherein: In step (3), the solvent replacement is to completely immerse the hydrogel in an ethylene glycol aqueous solution for 2 to 4 hours, and partially replace the water molecules in the hydrogel with the ethylene glycol solution.
8. Use of the ultra-high stretchable conductive hydrogel material according to any one of claims 1 to 7 in the preparation of a strain-type flexible sensor.
Citation Information
Patent Citations
Ti<3>C<2>T<x> composite double-network hydrogel and preparation and application thereof
CN110760075A
Zwitter-ion hydrogel electrolyte as well as preparation method and application thereof
CN117292950A
Cited By
Preparation method of super-strong and super-tough conductive hydrogel for retarding crack growth by submicron carbon clusters
CN119842015A
Water-retaining and sand-fixing biomass hydrogel material with function of monitoring water content
CN119899319A
